Excitation Kinetics of Impurity Doped Quantum Dot Triggered by Gaussian White Noise. (25th May 2013) - Pal, Suvajit; Sinha, Sudarson Sekhar; Ganguly, Jayanta; Ghosh, Manas
Abstract : We investigate the excitation kinetics of a repulsive impurity doped quantum dot initiated by the application of Gaussian white noise. In view of a comprehensive research we have considered both additive and multiplicative noise (in Stratonovich sense). The noise strength and the dopant location have been found to fabricate the said kinetics in a delicate way. Moreover, the influences of additive and multiplicative nature of the noise on the excitation kinetics have been observed to be prominently different. The investigation reveals emergence of maximization and saturation in the excitation kinetics as a result of complex interplay between various parameters that affect the kinetics. The present investigation is believed to provide some useful perceptions of the functioning of mesoscopic systems where noise plays some profound role.